The TV human capital: the associative movement of TV viewers in Spain - Rosique Cedillo, Gloria; García García, Francisco (Estudios sobre el Mensaje Periodístico, 2012)
In the present sector of TV contents prevails the lack of creativity and quality. Nevertheless this tendency seems to be changing with the participation of the citizenship organized in “associations of TV viewers”. These associations have been developing practices of control to regulate the audio-visual companies and the TV contents, betting by the self-regulation in the audiovisual sector. These actions could be affecting the exercise of the different TV agents, which would cause the revision of the theory of means and would open new discussions on the paradigms with which they come explaining the social phenomena from the communication.